Problems of the Secular State and Its Impact on Justice - Latief, Mohamad; Kusuma, Amir Reza; Muslih, Mohammad; Hidayatullah, Rakhmad Agung (Universitas Islam Negeri Raden Intan Lampung, 2023)
Every country has a goal to create prosperity for the whole society. Islam has exemplified that religion is closely related to the state. The implication of this relationship between ritual and politics has a very close relationship, it could be inseparable. But over time, the opinion emerged that religion and state should not unite, they argued that this separation could become active with modernization since religion can focus on spiritual affairs and political affairs can specifically regulate society. However, in practice it turns out that separation like a secular state has some significant impact on society. Therefore this article seeks to examine these problems through a literature review that is descriptive-analytical with an interdisciplinary approach, the analysis used is inductive analysis and content analysis. The results of this study show that the conception of a secular state aimed at making a Muslim better, seems to be a mere utopia. The impact of a secular state such as racism and capitalism is very detrimental to the people who are excluded. Ideologically and practically, the conception of a secular state is incompatible with Islamic values, because the Prophet Muhammad did not only teach religious affairs, but also taught political issues, even the Prophet Muhammad gave an example as a politician while in Medina and became a state administrator.